Hyponatremia as a Mortality Predictor of Severe Malaria: A Hospital Based Cross-sectional Study - Manoj Parida; Pravat Kumar Thatoi; Anurag Choudhury; Subhas Bhuin; Sarita Behera; Rina Mohanty (Journal of Clinical and Diagnostic Research, 2019)
Introduction: It is well known that hyponatremia is common in severe malaria. However, there is scanty and conflicting literature regarding hyponatremia as a predictor of mortality in severe malaria. Aim: To determine the prevalence of hyponatremia in severe malaria and its association with mortality. Materials and Methods: It was a hospital based cross-sectional study conducted in a tertiary care referral hospital in the state of Odisha in India. Sample size was calculated to be 99 by using the prevalence of hyponatremia in severe malaria 55% with absolute precision of 10%. Taking into account of 10% drop out rates, the final sample size was determined to 109. Considering the prevalence of mixed plasmodium infection to be 13% and the proportion of falciparum to vivax infection to be 49:51, samples ≥45 in each group was adequate for comparison. Consecutive sampling was done over a period of two years. Severe malaria included either infection with Plasmodium falciparum alone or both Plasmodium falciparum and Plasmodium vivax along with any one feature of WHO criteria for severity. Patients aged more than 15 years with both smear positive and rapid card test positive were included. Vital parameters and electrolyte levels were measured for each patient. The data was analysed using SPSS and significance level was set at 95%. Results: Out of the total number of 110 cases of severe malaria, isolated falciparum malaria was 57.3% (n=63) vs. mixed falciparum-vivax infection of 42.7% (n=47); overall mortality was 6.3% (n=4) vs. 14.8% (n=7) respectively. Hyponatremia was observed in 63.6% (n=70) of the total cases. The difference in incidence of hyponatremia in both the groups was 133±6 mEq/L vs. 127±6.3 mEq/L respectively and was statistically significant. Among the hyponatremic group of patients, the difference in level of sodium in both the group was (128±3.5 vs. 124±3.2) mEq/L and was statistically significant. Overall mortality rate was 10% (n=11/110), however mortality rate among the hyponatremic patients was 15.7% (n=11/70; 12.1% vs. 18.9% in both the groups respectively). Hyponatremia at a cut-off of 126 mEq/L predicted mortality with a sensitivity of 81.8%, specificity of 78.8%, and negative predictive value of 97.5%. Conclusion: Hyponatremia was highly prevalent among the severe malarial patients. Higher degree of hyponatremia was observed in mixed plasmodium infection. Severe hyponatremia predicted mortality with high sensitivity and specificity.